Diversity and abundance of plankton community in Tawang and Prigi Bays, natural settlement habitats of Spiny Lobster larvae in East Java, Indonesia - ENDANG DEWI MASITHAH; MUHAMMAD GIANO FADHILAH; MUHAMAD AMIN; KURNIATI UMRAH NUR; LAILA MUSDALIFAH; SHIFANIA HANIFA SAMARA; YUDI CAHYOKO; ALIMUDDIN ALIMUDDIN; SAHRUL ALIM; BAGUS DWI HARI SETYONO (Society for Indonesian Biodiversity, 2023)
Abstract. Masithah ED, Fadhilah MG, Amin M, Nur KU, Musdalifah L, Samara SH, Cahyoko Y, Alimuddin, Alim S, Setyono BDH. 2023. Diversity and abundance of plankton community in Prigi and Tawang Bays, natural settlement habitats of Spiny Lobster larvae in East Java, Indonesia. Biodiversitas 24: 1642-1649. Prigi and Tawang Bays have been well-known as settlement areas for spiny lobster larvae, Panulirus spp., in East Java, Indonesia. These locations may suggest suitable environments including diet availability for lobster larvae. Therefore, the present study aimed to investigate the type and abundance of plankton in both locations to discover potential live diets for lobster larvae. This study also explored plankton’s diversity, uniformity, and dominance indices in both locations. Plankton samples in each location were collected using a plankton net at four depths: 0.3 m, 2.5 m, 5 m, and 20 m with three replicates. The results revealed that 17 plankton species were identified from 0.30 m depth, 13 at 2.5 m, 11 at 5 m, and 13 at 20 m depth at Prigi Bay. In addition, 17 plankton species were discovered at 0.3 m depth, 11 at 2.5 m, 12 at 5 m, and 12 at 20 m at Tawang Bay. Among the most abundant species were Acartia sp., Calanus sp., Paracyclopina sp., and Oithona sp. The diversity indices observed in Karanggongso of Prigi Bay and Tawang Bay ranged from 2.02-2.49 and 2.17-2.65, respectively, within the moderate range. Similarly, the uniformity indices observed at both locations were moderate, ranging from 0.38-0.45 at Prigi Bay and 0.41-0.46 at Tawang Bay. There were no dominant species at both locations, as the dominance index values ranged from 0.13-0.30. Among the identified plankton species, Oithona sp., Calanus sp., Paracyclopina sp., and Acartia sp. are considered potential live feed for lobster larvae, and thus should be further studied.